The Influence of Digital Marketing and After Sales Service in Online Shopping Towards Purchasing Decisions - Luluk Nur Azizah; Muhamad Imam Syairozi (Journal of Economics and Management, 2026)
The rapid development of technology has strongly shaped human lifestyles, particularly in online shopping behavior. In response, businesses increasingly depend on digital marketing and after-sales service to attract customers and maintain satisfaction in a highly competitive digital environment. Nevertheless, many previous studies have examined these two factors separately, and only a limited number have explored how both jointly influence consumers' purchasing decisions in online shopping contexts. This research therefore investigates the effects of digital marketing and after-sales service on purchasing decisions in online shopping among consumers in Lamongan District, Indonesia. A quantitative method was applied using purposive sampling, involving 130 respondents who met the criteria of residing in Lamongan District, having made at least one online purchase within the last six months, and having experienced digital marketing promotions and after-sales services during the purchasing process. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach with SmartPLS 3.0. The findings indicate that both digital marketing and after-sales service have a positive and statistically significant effect on purchasing decisions. After-sales service exerts a stronger influence, positioning it as the dominant predictor. These results suggest that online businesses should not only prioritize marketing strategies but also strengthen their after-sales service systems to build customer trust, enhance satisfaction, and encourage purchasing decisions. Strong after-sales service can serve as a key competitive advantage in fostering long-term customer relationships and ensuring business sustainability.